"Terrified of a System I Didn't Understand": Reporting Staff Sexual Misconduct Against Women on Parole. (April 2022) - Darcy, Kathleen; Fedock, Gina; Kubiak, Sheryl Pimlott
Incarcerated women experience staff-perpetrated sexual victimization at high rates, yet limited research exists regarding women's experiences of this victimization while on probation and parole, particularly regarding their formal reporting decisions. This qualitative study explored the formal reporting decisions for 10 women who experienced staff-perpetrated sexual victimization while on parole. Women who formally reported their victimization experiences qualitatively differed from non-reporting women in terms of the dynamics and their identification of victimization (e.g., viewing as support vs. fear) and in the types of structural barriers (e.g., vulnerability and cautionary tales) they encountered. These findings highlight policy, practice, theory, and research directions.